Digital photographic practices as expressions of personhood and identity: variations across school leavers and recent retirees. Issue 4 (2nd October 2017) - Orzech, Kathryn M.; Moncur, Wendy; Durrant, Abigail; James, Stuart; Collomosse, John
Abstract : Over the last two decades, digital photography has been adopted by young and old. Many young adults easily take photos, share them across multiple social networks using smartphones, and create digital identities for themselves consciously and unconsciously. Is the same true for older adults? As part of a larger mixed-methods study of online life in the UK, we considered digital photographic practices at two life transitions: leaving secondary school and retiring from work. In this paper, we report on a complex picture of different kinds of interactions with visual media online, and variation across age groups in the construction of digital identities. In doing so, we argue for a blurring of the distinctions between Chalfen's 'Kodak Culture' and Miller and Edwards' 'Snaprs'. The camera lens often faces inwards for young adults: tagged 'Selfies' and images co-constructed with social network members commonly contribute to their digital identities. In contrast, retirees turn the camera's lens outwards towards the world, not inwards to themselves. In concluding, we pay special attention to the digital social norms of co-creation of self and balancing convenience and privacy for people of varying ages, and what our findings mean for the future of photo-sharing as a form of self-expression, as today's young adults grow old and retire.